RaÊ¼yu MuassisÄ« JÄmiÊ»ati al-RÄyah fÄ« al-BÄ«Ê¼ah al-Lugawiyyah al-Muá¹¡lÄ litaÊ»lÄ«m al-Lugah al-Ê»Arabiyyah - Saepudin, Asep Ahmad; Syihabuddin, Syihabuddin; Ali, Mad (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2021)
There are many educational institutions that have built the linguistic environment for teaching Arabic in Indonesia. But some of that linguistic environment was not quite right. This study seeks to reveal the optimal linguistic environment for teaching Arabic from founders of Arraayah University. The researcher used the descriptive approach. The researcher followed the observation, interview, and documentation method. The data was analyzed through descriptive analysis. The study concluded that the optimal linguistic environment is to be formed by providing several basic elements, namely: First, clarity of vision, mission and goal of the educational institution. Second, the existence of regulations. Third, human resources have a positive interaction towards the application of the Arabic. Fourth, regular study in the classroom on the basic of the application of the Arabic language. The researcher suggested a study about Implementation of linguistic environment in educational institution to develop the skill of listening and speaking.